PROSPECT OF SEAWEED AS ENVIRONMENTALLY FRIENDLY RAW MATERIALS FOR PAPER INDUSTRY - Kustantiny, Anny (Jurnal Rekayasa Lingkungan)
Seaweed is a commodity which has great potency to be developed and commonly used in food and non-food industry, such as cosmetic and pharmaceutical. Currently, seaweed can also be utilized as raw material for pulp to support an environmental friendly paper industry. Research has been done by scientists from Korea who developed the processing technology of red algae by using extraction and bleaching process. The process is very simple, need less energy and environmental friendly chemical material. Red algae species which is used in this process is Gelidium amansii, which is very suitable for paper industry purposes and can be harvested in around 3 months, therefore this is different with wood pulp. There is a cooperation between Korea and Indonesiain producing Gelidium in Indonesia. This paper presents the assessment of red algae pulp processing technology and examines several matters that should be considered in developing red algae pulp industry in Indonesia. In term of resources, support from the government, universities and research institutions and acceptance of the industry.keywords : seaweed, red algae, extraction, paper, environment